Cationic LNP-formulated mRNA expressing Tie2-agonist in the lung endothelium prevents pulmonary vascular leakage - Katrin Radloff; Birgitt Gutbier; Charlotte Maeve Dunne; Hanieh Moradian; Marko Schwestka; Manfred Gossen; Katharina Ahrens; Laura Kneller; Yadong Wang; Akanksha Moga; Leonidas Gkionis; Oliver Keil; et al. (Elsevier, 2023)
Dysfunction of endothelial cells (ECs) lining the inner surface of blood vessels are causative for a number of diseases. Hence, the ability to therapeutically modulate gene expression within ECs is of high therapeutic value in treating diseases such as those associated with lung edema. mRNAs formulated with lipid nanoparticles (LNPs) have emerged as a new drug modality to induce transient protein expression for modulating disease-relevant signal transduction pathways. In the study presented here, we tested the effect of a novel synthetic, nucleoside-modified mRNA encoding COMP-Ang1 (mRNA-76) formulated into a cationic LNP on attenuating inflammation-induced vascular leakage. After intravenous injection, the respective mRNA was found to be delivered almost exclusively to the ECs of the lung, while sparing other vascular beds and bypassing the liver. The mode of action of mRNA-76, such as its activation of the Tie2 signal transduction pathway, was tested by pharmacological studies in vitro and in vivo in respective mouse models. mRNA-76 was found to prevent lung vascular leakage/lung edema as well as neutrophil infiltration in a lipopolysaccharide-challenging model.